Web-Based Accounting Information System Design for Income Statements: a Case Study at Toko Amanah Kepanjen - Kinasih, Asti Sekar; Kusmintarti, Anik; Ekasari, Kurnia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to offer an efficient business process modeling solution to address issues in preparing the income statement for Toko Amanah Kepanjen. This study is a Research and Development (R&D) project that employs the ADDIE method, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. This method aids in designing a system that can identify and solve problems with a structured and systematic approach. The results indicate that the implementation of a web-based system is crucial to replace the existing manual system. The current manual system faces various issues, including difficulties in tracking revenue, inefficient data management, and the risk of human error in recording transactions. By implementing a web-based system, these issues can be effectively addressed through automation and data integration, thereby enhancing accuracy, efficiency, and transparency in the processes of booking and ready stock sales. The system also facilitates faster and more accurate reporting, and supports strategic decision-making based on reliable information.